Electrochemical and Spectroscopic Studies on the Interaction Between Tetracoordinate Macrocyclic Copper(II) Complex and DNA - Zhang, Shu-Sheng; Niu, S.Y.; Jie, G.F.; Jiao, K. (Asian Journal of Chemistry, 2016)
The crystal structure of tetracoordinate macrocyclic copper(II) complex ([CuL]I2.H2O, CuL) was determined by X-ray crystallography. The interaction of tetracoordinate macrocyclic copper(II) complex (CuL) with DNA in 0.1 mol L–1 Na2HPO4–NaH2PO4 buffer solution (pH 6.5) was studied by differential pulse voltammetry, cyclic voltammetry and UV/Vis spectroscopy. The observed oxidative peak from differential pulse voltammogram was shown at the glassy carbon electrode. It has been found that the oxidative peak current decreased significantly in the presence of DNA compared with that in the absence of DNA. At the same time, the absorbance of CuL at its absorption peaks also decreased with increasing concentration of DNA, but no obvious shift was observed. All experimental results indicate that CuL could interact with DNA mainly by electrostatic interaction and form a 1 : 1 DNA-CuL association complex with a binding constant of 1.02 × 104 mol-1 L.